2017
DOI: 10.1016/j.addbeh.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Ten-Item Internet Gaming Disorder Test (IGDT-10) and evaluation of the nine DSM-5 Internet Gaming Disorder criteria

Abstract: Introduction: The inclusion of Internet gaming disorder (IGD) in the DSM-5 (Section 3) has given rise to much scholarly debate regarding the proposed criteria and their operationalization.The present study's aim was threefold: to (i) develop and validate a brief psychometric instrument (Ten-Item Internet Gaming Disorder Test; IGDT-10) to assess IGD using definitions suggested in DSM-5, (ii) contribute to ongoing debate regards the usefulness and validity of each of the nine IGD criteria (using Item Response Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
275
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(309 citation statements)
references
References 25 publications
(35 reference statements)
26
275
2
6
Order By: Relevance
“…Specifically, relapse (unsuccessful attempts to stop or reduce), conflict (deceiving others), and withdrawal and problems (loss of interests) were the GAS items with a higher ability to discriminate IGD (endorsed more frequently in more severe IGD stages), whereas the items related to tolerance, salience (preoccupation), and mood modification (escape) were endorsed more widely among participants (included in less severe IGD stages). The results regarding preoccupation and escape were in concordance with those reported in previous studies [59,61] that showed large endorsement of the criteria. As reported in other studies, loss of interests [58,59], unsuccessful attempts to reduce or stop [59], deceiving others [59], and withdrawal [58,59] were more endorsed among participants with more severe IGD.…”
Section: The Igd Criteria Debatesupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, relapse (unsuccessful attempts to stop or reduce), conflict (deceiving others), and withdrawal and problems (loss of interests) were the GAS items with a higher ability to discriminate IGD (endorsed more frequently in more severe IGD stages), whereas the items related to tolerance, salience (preoccupation), and mood modification (escape) were endorsed more widely among participants (included in less severe IGD stages). The results regarding preoccupation and escape were in concordance with those reported in previous studies [59,61] that showed large endorsement of the criteria. As reported in other studies, loss of interests [58,59], unsuccessful attempts to reduce or stop [59], deceiving others [59], and withdrawal [58,59] were more endorsed among participants with more severe IGD.…”
Section: The Igd Criteria Debatesupporting
confidence: 91%
“…The following 4 criteria, described by some authors of core addiction criteria [20,30], received more consensus than the other criteria did: unsuccessful attempts to reduce or stop [4]; loss of interest in previous hobbies or activities [32,58,59]; continue despite problems [4,30,59]; and jeopardized or lost a relationship, job, or educational or career opportunity [59]. When observing such criteria, careful attention must be paid to possible coping motives (ie, related to a depressive disorder) before attributing any such symptoms to addictive behavior [58,60].…”
Section: The Igd Criteria Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Although IGD is not yet recognized as an official clinical entity (16), several new promising psychometric tools covering the nine IGD criteria have been developed following the formal recognition of this condition by the APA in May 2013 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Although the field of IGD is still in its early infancy, based on the latest progresses the field have witnessed, the following recommendations are made to help move forward and improve future research on IGD: (i) more scientific scrutiny is needed on each IGD criterion in terms of the impact and weight they may carry towards the final diagnosis, (ii) existing assessment tools would greatly benefit from further clinical studies utilizing actual clinically diagnosed samples so more concrete information on the validity and diagnostic properties (e.g., sensitivity, specificity, negative and positive predictive values) of these tools could be gathered, (iii) acquiring further longitudinal evidence on IGD is paramount for understanding the potential etiological mechanisms and clinical course of the disorder, such studies might provide useful evidence supporting the recognition of IGD as an official disorder, and (iv) large-scale nation-wide studies using probability samples and the already available new standardized psychometric tools are needed in order to estimate robust prevalence rates of IGD that can then be contrasted with prevalence rates found elsewhere, and that can be reliably be used by governmental bodies and other stakeholders in the process of policy making and development of adequate treatment protocols needed for this disorder [16,17]. A criterion is endorsed when a participant provides the maximum response possible in that item (i.e., 'Very often').…”
Section: Introductionmentioning
confidence: 99%